MEMBINA KECERDASAN SPIRITUAL ANAK Sebuah Kecerdasan yang Terabaikan - Abu Hasan Agus R (LP2M Universitas Ibrahimy, 2014)
Child is a precious gift, that every movement and activity of the child's represents his future will be passed. The intelligence grows more up every day. Therefore it must always be monitored to get information to assist and help his potential.The more urgent is the attention of training and develop the spiritual intelligence. spiritual intelligence will be established personality and character’s spiritual to be good human.